Inhibition of CFTR-mediated intestinal chloride secretion by a fungus-derived arthropsolide A: Mechanism of action and anti-diarrheal efficacy - Nattaphong Akrimajirachoote (2020)
© 2020 Elsevier B.V. Secretory diarrhea is one of the most common types of diarrhea with high morbidity and mortality. Previous studies showed that inhibition of cystic fibrosis transmembrane conductance regulator (CFTR) Cl- channels alleviated fluid loss in secretory diarrheas. This study aimed to identify novel CFTR inhibitors from fungal metabolites and explore its underlying mechanisms and potential utility in secretory diarrheas. Electrophysiological analyses in human intestinal epithelial (T84) cells were performed to investigate the effect and mechanism of fungal metabolites on CFTR-mediated Cl- secretion. Anti-diarrheal efficacy and the effect of compound on fluid absorption were investigated in mouse closed-loop models. We found that the screening identified arthropsolide A, a fungal metabolite from an endophytic fungus Roussoella sp. PSU-H51, as an inhibitor of CFTR-mediated Cl- secretion in T84 cells (IC50 ~0.8 μM). Arthropsolide A inhibited both CFTR and cAMP-activated basolateral K+ channels. Arthropsolide A had no effect on Na+-K+ ATPase activity. Interestingly, the inhibitory effect of arthropsolide A on CFTR was attenuated by cell depolarization and AMPK inhibition independent of multi-drug resistance protein 4, phosphodiesterases, and protein phosphatases. Importantly, arthropsolide A suppressed cholera toxin (CT)-induced Cl- secretion in T84 cells and CT-induced intestinal fluid secretion in mice by ~75% without affecting intestinal fluid absorption. Taken together, arthropsolide A represents a novel class of fungal metabolites that acts as a potent CFTR inhibitor. Further development of this class of compounds may provide a therapy for secretory diarrheas.